Reflection In The Writing Classroom - Yancey, Kathleen (University Press of Colorado, 1998)
Yancey explores reflection as a promising body of practice and inquiry in the writing classroom. Yancey develops a line of research based on concepts of philosopher Donald Schon and others involving the role of deliberative reflection in classroom contexts. Developing the concepts of reflection-in-action, constructive reflection, and reflection-in-presentation, she offers a structure for discussing how reflection operates as students compose individual pieces of writing, as they progress through successive writings, and as they deliberately review a compiled body of their work-a portfolio, for example. Throughout the book, she explores how reflection can enhance student learning along with teacher response to and evaluation of student writing. Reflection in the Writing Classroom will be a valuable addition to the personal library of faculty currently teaching in or administering a writing program; it is also a natural for graduate students who teach writing courses, for the TA training program, or for the English Education program.